2019
DOI: 10.3390/antiox8060166
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Tea and Its Bioactive Compounds for the Prevention and Treatment of Cardiovascular Diseases: An Updated Review

Abstract: Cardiovascular diseases (CVDs) are critical global public health issues with high morbidity and mortality. Epidemiological studies have revealed that regular tea drinking is inversely associated with the risk of CVDs. Additionally, substantial in vitro and in vivo experimental studies have shown that tea and its bioactive compounds are effective in protecting against CVDs. The relevant mechanisms include reducing blood lipid, alleviating ischemia/reperfusion injury, inhibiting oxidative stress, enhancing endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 96 publications
1
50
0
Order By: Relevance
“…Recent mechanistic studies have examined the effects of green tea intake on lipid control and provide further evidence for the biological plausibility of these findings. In accordance with our results, several animal studies have reported that green tea supplementation significantly improved hyperlipidemia status in high-fat diet induced rats, including lowering TC, LDL cholesterol, and triglycerides [54]. Moreover, recent animal studies have indicated that green tea catechins could significantly inhibit atherosclerotic plaque formation, lower liver fat accumulation, and increase HDL cholesterol in hyperlipidemic rats induced by high-fat andhigh-cholesterol diet [55].…”
Section: Discussionsupporting
confidence: 92%
“…Recent mechanistic studies have examined the effects of green tea intake on lipid control and provide further evidence for the biological plausibility of these findings. In accordance with our results, several animal studies have reported that green tea supplementation significantly improved hyperlipidemia status in high-fat diet induced rats, including lowering TC, LDL cholesterol, and triglycerides [54]. Moreover, recent animal studies have indicated that green tea catechins could significantly inhibit atherosclerotic plaque formation, lower liver fat accumulation, and increase HDL cholesterol in hyperlipidemic rats induced by high-fat andhigh-cholesterol diet [55].…”
Section: Discussionsupporting
confidence: 92%
“…Catechins are the principal components of tea antioxidant polyphenols, which mainly include two non-ester catechins, (−)-epicatechin (EC) and (−)-epigallocatechin (EGC), and two ester catechins, (−)-epicatechin gallate (ECG) and (−)-epigallocatechin gallate (EGCG) [ 3 , 4 ]. These catechins show potential health benefits, such as anticancer, anti-obesity, antibacterial, antioxidant, and antiviral effects [ 5 , 6 , 7 , 8 ]. Nowadays, catechins have been widely applied in the pharmaceutical and food industry.…”
Section: Introductionmentioning
confidence: 99%
“…There are diverse studies pointing out the effect of EGCG on in vitro cell cultures or in vivo based on animal models, as reviewed, for example, in Khan and Mukhtar [5]. Human studies focus, on the majority, on epidemiological evaluations, and few are based on clinical data from conventional blood analysis, as conducted over cancer development and progression [10], metabolic syndrome [11], and cardiovascular diseases [12,13]. Human studies using catechins as a supplement observed a decrease of plasma Low-Density Lipoproteins (LDL) in comparison with controls, and in smokers a reduction of benzo[a]pyrene adducts [14][15][16].…”
Section: Introductionmentioning
confidence: 99%